Using Diffusion To Characterize Interfacial Heterogeneity - Kijewska, Krystyna (Langmuir : the ACS journal of surfaces and colloids, 2017)
We report on the use of molecular diffusional motion over a range of length scales to characterize compositional heterogeneity in monolayer structures. This work focuses on the diffusional motion of perylene in two types of films supported on functionalized silica surfaces: single-component (stearic acid) and two-component (hydrocarbon/fluorocarbon) films. Langmuir-Blodgett (LB) monolayers were deposited directly on silica or were bound to surface-modified silica by means of metal ion complexation. The LB films were characterized by their π-A isotherms and by Brewster angle microscopy (BAM) during formation and deposition. Chromophore mobility and monolayer structural heterogeneity were evaluated by comparing rotational diffusion data (fluorescence anisotropy decay imaging) and translational diffusion data (fluorescence recovery after photobleaching) on the same LB films. Our results indicate that the mobility of the chromophore depends sensitively on both metal ion identity and film composition